'Doing good and feeling good': how narratives in development stymie gender equality in organisations. Issue 3 (21st March 2022) - Wu, Joyce
Abstract: This paper examines the challenges of working on gender equality in international development research projects and institutes, and how a code of appropriate emotions and behaviours is used to silence and stifle institutional change. Using my own experience at a science research institute, I argue that while senior leaders have acknowledged the importance of equity and diversity, internal institutional dynamics, workplace culture and hierarchies make change difficult. Furthermore, due to the nature of international development work, there is an affective norm ('doing good and feeling good') that surrounds the notion of working in 'developing' countries. This affect is gendered because a masculine camaraderie is generated. However, the affect shuts out self-reflexivity, because it would disrupt the narrative of selflessness and heroism of aid. The inside activists within the institute navigate between challenging the norms and having an unspoken code of civility imposed upon them, which is used to police and discipline how inside activists should behave. When inside activists criticise discriminatory practices and values, they are dismissed as being 'angry' and 'uncivil'. The result is the depoliticisation of gender and feminist theories and practice, where people go through the motions of equity and mainstreaming without achieving meaningful change.